"I Think She's Learnt Her Lesson": Juror Use of Cultural Misconceptions in Sexual Violence Trials - Tinsley, Yvette; Baylis, Claire; Young, Warren (Victoria University of Wellington Law Review, 2022)
The extent to which decision-making in sexual violence jury trials is impacted by culturally embedded misconceptions is not well understood. In this article, we provide an insight into the views of 121 real jurors in 18 sexual violence trials, illustrating that rape myth acceptance scales give an incomplete view of when and how jurors might be influenced by cultural misconceptions. Prompted in part by the behaviour and tactics of counsel, jurors in real trials often expect complainants to fight back and to report sexual offending immediately. They also have expectations of complainants and defendants that derive from misconceptions about "real rape". While our study confirms that jurors are susceptible to cultural misconceptions, it also demonstrates the complexity of assessing the extent of their influence and the difficulties in designing reforms to reduce their use.